A framework for ecologically and socially informed risk reduction before and after outbreaks of wildlife-borne zoonoses - Hassell, James M.; Angwenyi, Shaleen; VanAcker, Meredith C.; Adan, A.; Bargoiyet, Nelly; Bundotich, G.; Edebe, J.; Fèvre, Eric M.; Gichecha, P.; Kamau, J.; Lekenit, E.; Lekopien, A.; et al. (Elsevier, 2025)
Despite increasing emphasis being placed on the inclusion of upstream ecological and social perspectives for zoonotic disease control, few guidelines exist for practitioners and decision makers to work with communities in identifying suitable, locally relevant interventions and integrating these into public health action plans. With an interdisciplinary group of Kenyan stakeholders, we designed and tested a comprehensive framework for the co-design, evaluation, and prioritisation of beneficiary-oriented, ecologically and socially informed interventions for preventing and controlling outbreaks of wildlife-borne zoonoses. Our approach used four globally important wildlife-borne pathogens—Rift Valley fever virus, Congo–Crimean haemorrhagic fever virus, and the causative agents of anthrax and rabies—enabling stakeholders to develop a shared understanding of complex transmission pathways, identify a broad array of measures targeting ecological, biological, and social processes governing outbreaks of these pathogens, and explore trade-offs for specific interventions. The framework can be applied early in the decision-making process to encourage broader, cross-sectoral co-production of knowledge, ideas, and consensus on the control of complex zoonotic diseases.